Acknowledgement to reviewers Metalurgija 61 (2022) 1-4, 1–896 - Ilija Mamuzić (Metalurgija, 2022)
The Editorial Board of Journal Metalurgija gratefully acknowledges assistance given during 2022; Metalurgija 61 (2022) 1-4, 1- 896 to all of their Reviewers. The full list of reviewers for the year 2022 is given.